Decreased expression of fibroblast growth factor 13 in early-onset preeclampsia is associated with the increased trophoblast permeability - Yue, Xiaojing; Sun, Ying; Zhong, Mei; Ma, Yanlin; Wei, Yanxing; Sun, Fei; Xiao, Lu; Liu, Mian; Chen, Jianing; Lai, Yingjun; Yan, Chuming; Huang, Liping; et al. (Placenta (Eastbourne), 2018)
Intracellular protein fibroblast growth factor 13 (FGF13) is highly expressed in human placenta, although its biological function remains unexplored. The aims of this study were to investigate the expression of FGF13 in placentae with early-onset preeclampsia (PE) and the associated mechanisms in the pathophysiology of PE. The expression levels of FGF13 in placentae obtained from patients with early-onset PE and normal pregnancies were assessed using immunofluorescent staining, Western blot assays and quantitative PCR. We knocked down FGF13 in trophoblast cell lines BeWo and HTR8/SVneo, and analyzed cell permeability. Clinical trophoblast cell-cell junctions were identified by cytokeratin 7 (CK7) immunofluorescent staining of human placental sections. The expressions of FGF13 were manipulated in BeWo and HTR8/SVneo cell lines, and the expressions of E-cadherin were quantified by reverse transcription followed by quantitative PCR, Western blot assays and immunofluorescent staining. The expressions of FGF13 and E-cadherin were further confirmed in the isolated human primary trophoblasts. Downregulation of FGF13 along with trophoblast disarrangement were found in human placentae with early-onset PE. In trophoblast cell lines decreased FGF13 expression resulted in increased cell permeability and decreased E-cadherin expression. The FGF13 insufficiency-mediated loss of E-cadherin was further confirmed in the human villous trophoblasts isolated from PE patients. FGF13 was downregulated in human placentae with early-onset PE. FGF13 played an important role in maintaining placental trophoblast permeability via the modulation of E-cadherin. •FGF13 was downregulated in human placental tissues with early-onset PE.•The early-onset PE placenta displayed disordered trophoblast arrangement.•Loss of FGF13 and E-cadherin were observed in primary human PE trophoblasts.•In FGF13-silenced trophoblasts, cellular permeability increased.•The level of FGF13 was positively associated with the level of E-cadherin.